A qualitative analysis of women’s reproductive agency and postpartum family planning in Maharashtra, India - Bhan, Nandita; Thomas, Edwin Elizabeth; Kully, Gennifer; Ghule, Mohan; Raj, Anita; McDougal, Lotus; Singh, Abhishek; Averbach, Sarah (PLOS ONE, 2025)
Background Despite the benefits of healthy birth spacing for mothers and infants, the use of postpartum family planning (PPFP) by women in India remains low. We qualitatively examined barriers to PPFP access and use to understand the intersections between women’s reproductive agency, fertility and contraceptive norms, and community interactions with health providers in rural Maharashtra, India. Methods We conducted 62 qualitative in-depth interviews with postpartum women, husbands and mothers-in-law of postpartum women, frontline health workers (FLWs) and key community stakeholders in rural Maharashtra from March to May 2022. Semi-structured interview guides included probes related to knowledge of and access to PPFP services, contraceptive decision-making dynamics, interactions with health providers, community norms related to fertility and family planning, and existing and aspirational models for PPFP service delivery. We used an inductive approach to organize emerging codes into themes using Bronfenbrenner’s Ecological Systems Theory, categorizing findings into a thematic framework to inform PPFP programming. Results Five key themes emerged: (1) Few women received PPFP counseling or services, with marginalized communities disproportionately affected by poor access. (2) Postpartum women lacked agency in contraceptive decision-making and often needed their husband’s approval to access PPFP services. (3) Clinicians identified misinformation, lack of education, and community beliefs in contraceptive myths for lack of informed choice. (4) While norms for limiting family size were strong, contraception was considered a ‘sensitive’ subject and sparked concerns regarding confidentiality in discussing PPFP. (5) Community reported that counseling services were prescriptive and lacked information on the side effects of contraception, leading to the perception of low-quality care and dissatisfaction with PPFP health services. Conclusions There is an urgent need to enhance PPFP counseling and service provision within family planning programs in India, emphasize reproductive choice among women, broaden the public dialogue on contraceptive use and find ways to engage men in contraceptive decision making. Interventions that can enhance knowledge and change acceptability of contraception in the community will enhance informed choice for contraceptive use among couples as well as PPFP access and use.